ChemInform Abstract: Oxidative Cyclization Reactions: Controlling the Course of a Radical Cation‐Derived Reaction with the Use of a Second Nucleophile. Issue 19 (13th May 2014) - Redden, Alison; Perkins, Robert J.; Moeller, Kevin D.
Abstract The intramolecular trapping of both ends of electrolytically generated enol ether radical cations is an efficient method for oxidative cyclization to furnish functionalized carbo‐ and heterocycles.